THE INFLUENCE OF PROFESSIONAL ETHICS E-MODUL AND LEGISLATION ON STUDENT COURSE GRADES - Rakhmawati, Rakhmawati; Syukriani, Yoni Fuadah; Husen, Ike Rostikawati; Damayanti, Dini Fitri (Poltekkes Kemenkes Pontianak, 2024)
Background: Ethics helps a person in taking the right attitudes and actions in life. By studying professional ethics and legislation, students are expected to be able to master factual knowledge about ethics and statutory law in midwifery care. There is concern with the hybrid learning model in the future, because the topic of professional ethics in hybrid learning can be difficult because the subjects are philosophical, legal and affective which are generally quite abstract. Purpose: this study was to analyze the effect of the e- Module on professional ethics and legislation on midwifery student course scores. Methods: This is quantitative research using a crossover design. The groups used in this research were 2 groups. The two groups were given the same material using different methods. The sampling technique is total sampling. Result: There was a significant difference between course scores before and after using the e-module (p<0.05) and there was a significant difference between the average course scores in the e-module group and the control group (p<0.05). However, there is no significant relationship between course grades and students' perceptions of e-modules (p>0.05). Results: The existence of the professional ethics and legislation e-module increased student course grades, and there was no strong significant relationship between course grades and perceptions